High titer HIV-1 V3-specific antibodies with broad reactivity but low neutralizing potency in acute infection and following vaccination - Davis, Katie L.; Gray, Elin S.; Moore, Penny L.; Decker, Julie M.; Salomon, Aidy; Montefiori, David C.; Graham, Barney S.; Keefer, Michael C.; Pinter, Abraham; Morris, Lynn; Hahn, Beatrice H.; Shaw, George M. (Virology (New York, N.Y.), 2009)
Identifying the earliest neutralizing antibody specificities that are elicited following infection or vaccination by HIV-1 is an important objective of current HIV/AIDS vaccine research. We have shown previously that transplantation of HIV-1 V3 epitopes into an HIV-2 envelope (Env) scaffold provides a sensitive and specific means to detect and quantify HIV-1 V3 epitope specific neutralizing antibodies (Nabs) in human sera. Here, we employ this HIV-2/HIV-1 V3 scaffolding strategy to study the kinetics of development and breadth of V3-specific Nabs in longitudinal sera from individuals acutely infected with clade C or clade B HIV-1 and in human subjects immunized with clade B HIV-1 immunogens. HIV-2/HIV-1 chimeras containing V3 sequences matched to virus type (HIV-2 or HIV-1), subtype (clade B or C), or strain (autologous or heterologous) were used as test reagents. We found that by 3–8 weeks post infection, 12 of 14 clade C subjects had a median IC 50 V3-specific Nab titer of 1:700 against chimeric viruses containing a heterologous clade C V3. By 5 months post-infection, all 14 subjects were positive for V3-specific Nabs with median titers of 1:8000 against heterologous clade C V3 and 1:1300 against clade B V3. Two acutely infected clade B patients developed heterologous clade B V3-specific Nabs at titers of 1:300 and 1:1800 by 13 weeks of infection and 1:5000 and 1:11000 by 7 months of infection. Titers were not different against chimeras containing autologous clade B V3 sequences. Each of 10 uninfected normal human volunteers who were immunized with clade B HIV-1 Env immunogens, but none of five sham immunized control subjects, developed V3-specific Nabs titers as high as 1:3000 (median 1:1300; range 1:700–1:3000). None of the HIV-1 infected or vaccinated subjects had antibodies that neutralized primary HIV-1 virus strains. These results indicate that high-titer, broadly reactive V3-specific antibodies are among the first to be elicited during acute and early HIV-1 infection and following vaccination but these antibodies lack neutralizing potency against primary HIV-1 viruses, which effectively shield V3 from antibody binding to the functional Env trimer.